2013
DOI: 10.1590/s1413-70542013000100005
|View full text |Cite
|
Sign up to set email alerts
|

Physiological quality and amylase enzyme expression in maize seeds

Abstract: The physiological quality of maize seeds is affected by the genotype. Thus, the study of expression of genes associated with this characteristic is important in the genotype selection process in breeding programs. The aim of this research was to study the expression of amylase enzymes associated with physiological quality of maize seeds with different genotypes and seed sizes. We further sought to assess the expression of these enzymes in dry and soaked seeds The experiment was conducted in the experimental ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 23 publications
(32 reference statements)
1
35
0
4
Order By: Relevance
“…However, Oliveira et al (2013) points out that in addition to the amylase genes, several other genes may be involved in controlling the physiological quality of seeds trait, as an example, the genes directly related to respiration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Oliveira et al (2013) points out that in addition to the amylase genes, several other genes may be involved in controlling the physiological quality of seeds trait, as an example, the genes directly related to respiration.…”
Section: Resultsmentioning
confidence: 99%
“…Andrade et al (2013), with assessments at the fourth and seventh day after seeding, accounting was used the methodology proposed by Oliveira et al (2013). The extraction of heat resistant proteins was performed according to the methodology described by Andrade et al (2013).…”
mentioning
confidence: 99%
“…Some research has shown that the physiological quality of maize seed (Zea mays) is inluenced not only by environmental factors, but also by the genotype and its interactions with the environment Importance of amylases in seed quality (HOECKER et al, 2006;REIS et al, 2011;OLIVEIRA et al, 2013;. Many authors such as Rood et al (1990), Causse et al (1995), Gomes et al (2000), José et al (2004b), Hoecker et al (2006 and Reis et al (2011) relate quality to the inluence of heterosis or hybrid vigor in seed germination.…”
Section: Developmentmentioning
confidence: 99%
“…Paleg (1965), in biochemical studies manipulating α-amylase synthesis and subsequent hydrolysis of the seed reserves, found a direct relationship between gibberellin synthesis and maize heterosis. According to Rood et al (1990) and Oliveira et al (2013), maize lineages are less vigorous than their descendant hybrids, in part because of gibberellin deiciency. These authors also found a positive correlation between seedling gibberellin content and growth rate, leaf area, and height of maize plants.…”
Section: Developmentmentioning
confidence: 99%
See 1 more Smart Citation